2011
DOI: 10.1016/j.ijgo.2011.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intravenous tranexamic acid administration on blood loss during and after cesarean delivery

Abstract: Intravenous tranexamic acid decreased intra- and postoperative blood loss and oxytocin administered in patients delivered by cesarean.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
107
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 118 publications
(129 citation statements)
references
References 8 publications
12
107
1
4
Order By: Relevance
“…Other haematological and biochemical parameters did not have any significant difference in the two groups. These results were comparable with the study by Movafegh et al [6] and Gai et al [7].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Other haematological and biochemical parameters did not have any significant difference in the two groups. These results were comparable with the study by Movafegh et al [6] and Gai et al [7].…”
Section: Discussionsupporting
confidence: 92%
“…Svanberg et al [10] reported 67 cases of abruptio placentae being treated by tranexamic acid without any signs of thrombosis in any. Similar results were found in other studies [6,7,9]. All data demonstrated that tranexamic acid can be used safely without increasing the occurrence of thrombosis, but still more studies are needed in this regard.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations